2017
DOI: 10.1039/c7cc05420c
|View full text |Cite
|
Sign up to set email alerts
|

In situ synthesis of Au-shelled Ag nanoparticles on PDMS for flexible, long-life, and broad spectrum-sensitive SERS substrates

Abstract: A simple and fast one-step fabrication method of silver nanoparticles (AgNPs) on a polydimethylsiloxane (PDMS) film and their improvement as highly sensitive surface enhanced Raman scattering (SERS) substrates via atomically thin Au coatings is demonstrated. The thin Au layer provides oxidation resistivity while maintaining the broad spectral range SERS sensitivity of Ag nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 34 publications
(46 reference statements)
3
45
0
Order By: Relevance
“…It is also noticed that the peaks around 700 and 800 cm −1 undergoes a blueshift as the increasing pH. The theoretically simulated pH‐dependent SERS of PMBA match quite well with experimentally measured results …”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…It is also noticed that the peaks around 700 and 800 cm −1 undergoes a blueshift as the increasing pH. The theoretically simulated pH‐dependent SERS of PMBA match quite well with experimentally measured results …”
Section: Resultssupporting
confidence: 83%
“…p ‐mercaptobenzoic acid (PMBA) and p ‐mercaptopyridine (PMPY) can be transformed to their corresponding conjugated base and acid during deprotonation and protonation processes. Thus, these two molecules are widely applied as pH sensors to determine the surface pK a by measuring the pH‐dependent SERS . Yu et al reported a SERS method to determine the pK a value by monitoring the SERS spectral changes of PMPY adsorbed on a buffer/gold interface .…”
Section: Introductionmentioning
confidence: 99%
“…Surface-enhanced Raman scattering (SERS) is a non-destructive and ultra-sensitive analytical technique, which allows rapid molecular-specific detection of a wide range of targets [1,2]. Since its discovery in 1974, SERS has been applied for the analytical sensing of many molecules of biological interest ranging from small organic molecules [3][4][5], pesticides [6,7] and drugs [8,9] to larger structures such as proteins, nucleic acids and cells [10][11][12][13]. Due to its promptness, high sensitivity and molecular specificity, SERS is particularly useful for drug detection.…”
Section: Introductionmentioning
confidence: 99%
“…The enhancement of Raman signals in SERS depends upon the intensification of the electromagnetic field of both incident and scattered radiation in the proximity of metal plasmon surfaces (electromagnetic enhancement), and/or upon the resonant or non-resonant energy transfer between the metal nanoparticle and the adsorbed molecule (chemical enhancement). Traditionally, silver-based nanomaterials are used in SERS applications, since this metal demonstrated to induce strong enhancement effects [8,9]; however, it has been already reported that silver nanostructures can easily oxidase at room temperature conditions [3] and show a strong tendency to growth and/or reshape upon prolonged irradiation [21,22]. For this reason, in recent years, the attention was focused on hybrid nanomaterials, in which the properties of two or more elements are combined in a single platform [5,7,[23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Raman spectra are then collected after a period of mixing, which is crucial for the metal-analyte interaction, as well as for the difficulty to guarantee the colloidal stability upon mixing with high ionic strength bio solutions [9]. Fortuni et al described a protocol for in situ growth of Au shelled Ag-NPs on polidymethylsiloxane (PDMS), which led to great polydispersity of NPs with consequent low reproducible fabrication of SERS-substrates [14]. Moreover, most of the SERS-microfluidic POC devices described, are coupled with Raman microscopes, which are expensive bench-top bulky instruments not always compatible with measurements in a clinical scenario [15][16][17].…”
mentioning
confidence: 99%